(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
In this article, detailed information is given about the importance of the rich heritage of the composer, artist, creative artist Mutal Burkhanov in the culture of Uzbek music and how he skilfully reworked folk songs